THEORETICAL AND LEGAL CHARACTERISTICS OF THE PREVENTION OF HARASSMENT AND VIOLENCE AGAINST WOMEN - Maktumova, Yulduz (Oriental Journal of History, Politics and Law, 2026)
This article analyzes issues related to the general description of the prevention of oppression and violence against women.In addition, this article also examines the general description of the prevention of oppression and violence against women from all aspects and its victimological aspects and components. It is also noted that in order to identify and eliminate the causes of oppression and violence against women and the conditions that allow them, a system of legal, social, organizational and other measures of general, special, individual and victimological prevention of violations can be taken.